Penatalaksanaan Fisioterapi Pada Pasca Operasi Fraktur Femur 1/3 Distal Dextra di RSUD Dr. Hardjono S. Ponorogo Dengan Modalitas Terapi Latihan - Saputro, Wahyu Panji, Wijianto, SSt.Ft., M.Or (2016)
Background: Fractures femur 1/3 distal is the loss of metaphysical discontinuity in the distal femur covering 8 to 15 cm distal of femur. The problem is pain, edema, limitation of Range of Motion (ROM), decreased muscle strength and functional ability. The modalities used are exercise therapy Aim: To find out the physiotherapy in reducing pain and edema, increase ROM, muscle strength and functional ability in the case of fracture distal 1/3 femur using exercise therapy modalities. Result: After 6 treatment the results is silent pain reduction T1: 1,5 cm to T6: 0 cm; tenderness T1: 4,9 cm to T6: 2,7 cm and painful motion T1: 5,9 cm to T6: 3,9 cm. Maleolus decrease edema in the medial (at 6 cm) of T1: 30 cm into T6: 28 cm; on the tuberosiy of tibia from T1: 56,5 cm to T6: 54,5 cm. Increased LGS hip of T1: S: 00-0-100 be T6: S: 100-0-600, increased LGS knee of T1: S: 00-0-100 be T6: S: 00-0-450. Increased muscle strength muscle hip abductor muscle T1: 3 to T6: 4, hip adductor of T1: 3 to T6: 4. Increased functional abilities of T1: not able to sit into T6: walking with cruck. Conclusion: Therapeutic exercise can reduce pain, swelling, increasing range of motion, muscle strength and functional ability.